The Indian Forest Rights Act (2006) and rights of forest-dwellers of Koraput, Odisha - Gaur, Kamla (2018)
This thesis is an intersectional study of forest rights of forest-dwellers in the tribal territory of Koraput, India. The thesis is developed around a piece of path-breaking legislation, the Forest Rights Act (FRA) of India 2006, under which land titles and resource use rights are being granted to many forest-dwelling households and communities.This work exclusively deals with the individual title holders of forest land under the FRA. It explores three important questions: 1) what is the history of forest-rights delineation in Koraput?, 2) how are the rights of forest-dwelling people being settled under FRA? and, 3) what are the complexities of land use in these tribal forestlands?}